Legal Protection for Children as Victims of Economic Exploitation: Problems and Challenges in Three Major ASEAN Countries (Indonesia, Vietnam and Philippines) - Utari, Indah Sri; Ramada, Diandra Preludio; Arifin, Ridwan; Smith, Robert Brian (Lex Scientia Law Review, 2023)
This research critically examines the legal safeguards for children facing economic exploitation in three prominent ASEAN countries: Indonesia, Vietnam, and the Philippines. Despite the presence of protective legislation in these nations, the effective implementation of these laws encounters significant obstacles. In Indonesia, diverse regulations intended to shield children from economic exploitation coexist with the persistent issue of child labor. The continued prevalence of child labor is attributed to inadequate enforcement of labor laws and a general lack of community awareness regarding children's rights. Vietnam, while boasting a relatively comprehensive legal framework against child labor, faces challenges in certain rural areas where instances persist due to entrenched issues like poverty, cultural traditions, and limited access to education. Moreover, in the Philippines, the government has implemented measures such as the Child Labor Law and the Anti-Child Trafficking Act to protect children from economic exploitation. However, the effectiveness of these initiatives is impeded by resource constraints, corruption, and limited community awareness. In conclusion, this study reveals that legal protection for children in Indonesia, Vietnam, and the Philippines is hindered by a range of challenges, including deficient enforcement mechanisms, enduring cultural traditions, widespread poverty, systemic corruption, and limited community awareness. Addressing these complex issues requires collaborative efforts from governments, civil society, and communities to ensure the robust protection of children's rights.